Building Energy Modeling with OpenStudio - Brackney, Larry; Parker, Andrew; Macumber, Daniel; Benne, Kyle (Springer, 2018)
This book is intended to provide advanced undergraduate and graduate students with an introduction to the topic of building energy modeling, simulation, analysis, and optimization. It is assumed that the reader has a basic understanding of fluid mechanics, thermodynamics, and heat transfer and is prepared to apply those fundamentals to more complex systems. The authors believe that this book will also be of value to energy efficiency professionals who are actively engaged in improving the built environment. A number of software tools exist to model and simulate individual buildings, and many of the concepts discussed in this text are applicable to them. That said, the authors have structured this book around an open-source platform called OpenStudio and its underlying EnergyPlus simulation engine. OpenStudio is intended to facilitate the creation of many tools that make use of energy simulation to enable decision-making by diverse stakeholders at each stage of a building’s lifecycle. The platform contains a number of attributes unique to energy modeling including an object-oriented data model, extensible scripting, and an analytical framework that scales from individual buildings up to portfolios. The reader will experience these and other features of OpenStudio and EnergyPlus throughout the book using a pair of example applications built with the platform. Instructors should find the material organized in a sequence that slowly builds in complexity, enabling students to gain fundamental knowledge while applying new skills as they progress. To that end, each chapter concludes with one or more “checkpoint” exercises, so-named because they generally result in a usable model that is built upon in a subsequent exercise. The authors consider the checkpoint exercises as integral to the book’s content, and we strongly urge students to work through them in their entirety. While we believe the exercises are organized in the most appropriate order, instructors can elect to have students work through checkpoints one and three before proceeding to checkpoints two, four, and onwards without impacting prerequisites for subsequent chapters. It is really up to the instructor’s preference as to whether they wish to maintain student focus on rudiments or begin mixing in sophisticated applications that expand on those fundamentals more rapidly.
A Practical Guide for Students and Professionals